Nell - Apted, Michael; Neeson, Liam.; Natasha Richardson; Nick Searcy; Richard Libertini; Robin Mullins; Jodie Foster (USA Egg Pictures, 1994)
Nell is a girl who's been brought up in an isolated world. The only person she knew was her mother and twin sister. They lived together in a cottage in the forest. Nobody has ever met Nell. After her mother's death, she's discovered by the local doctor Jerome. He's fascinated by her, since she speaks an mangled language, developed by her sister and herself growing up; "twin speak" if you will. But Paula, a psychology student, wants her observed in a laboratory. The judge decides they get three months to observe her in the forest, after which he'll decide about Nells future.
Nell is a girl who's been brought up in an isolated world. The only person she knew was her mother and twin sister...
Mark Handley
Languages : English, Turkish, German, French, Spanish
Subtitles : English, Turkish, German, French, Spanish
Keywords: Drama